PENGARUH MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR DESA CIDOKOM BOGOR - Ega Apitri; Tarwijo (Journal of Research and Publication Innovation, 2025)
This research aims to determine the influence of work motivation and work discipline on employee performance at the Cidokom Bogor Village Office. This type of research is quantitative research and the research method used is the associative method. The population of Cidokom Bogor Village Office employees is 51 people. Meanwhile, the sample used was 51 respondents using saturated sampling techniques. The analysis in this research used the SPSS version 25 program. The data analysis method used simple linear regression, multiple linear regression, correlation coefficient, coefficient of determination, partial t test and simultaneous F test. The research results show that: (1) There is a significant influence of work motivation on employee performance at the Cidokom Village Office, Bogor Regency with a sig value obtained of 0.000 < 0.05 with an R square coefficient of determination of 0.689, which means 68.9% of employee performance in The Cidokom Village Office, Bogor Regency is influenced by work motivation and the remaining 31.1% is influenced by other factors. (2) There is a significant influence of work discipline on employee performance at the Cidokom Village Office, Bogor Regency with a sig value obtained of 0.000 < 0.05 with an R square coefficient of determination of 0.738, which means 73.8% of employee performance at the Cidokom Village Office, Bogor Regency influenced by work discipline and the remaining 26.2% is influenced by other factors. (3) There is a significant influence of work motivation and work discipline on employee performance at the Cidokom Village Office, Bogor Regency with a sig value obtained of 0.000 < 0.05 with an R square coefficient of determination of 0.816, which means 81.6% of employee performance at the Village Office Cidokom Bogor Regency is influenced by work motivation and work discipline and the remaining 18.4% is influenced by other factors.